STRATEGIC APPROACHES TO STRENGTHENING STATE REGULATION OF THE REINSURANCE MARKET - SHKURKO, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Regulation of the reinsurance market in Ukraine faces many problems related to the development of market dynamics, emerging risks and regulatory gaps. Despite recent efforts to improve the regulatory framework, there remains a need to strengthen government regulation to ensure market stability, sustainability and competitiveness. Key issues are based on the adequacy of regulatory oversight, compliance with international standards and norms, promotion of innovation and protection of consumer rights. The reinsurance market in Ukraine is an important component of the insurance industry, contributing to risk management and ensuring financial stability. However, effective state regulation is essential for addressing challenges, harnessing opportunities, and promoting sustainable growth in this sector. The article examines the current state of state regulation of the reinsurance market in Ukraine. The current state of regulation of the reinsurance market in Ukraine is analyzed, strengths and weaknesses are identified, and directions for improvement are formed. The problems encountered by the National Bank of Ukraine (NBU) in fulfilling its regulatory and supervisory functions over the reinsurance market have been analyzed, and vectors of influence by the regulator have been formed to improve regulation of the reinsurance market. A strategy for strengthening state regulation of the reinsurance market in Ukraine is provided, based on the results of recent research and international best practices. The proposed strategy for enhancing regulatory oversight will promote market development by creating clear regulatory frameworks and strengthening solvency and risk management standards.